2020
DOI: 10.1002/mrm.28164
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of spectra from truncated free induction decays by deep learning in proton magnetic resonance spectroscopy

Abstract: Purpose:To explore the applicability of convolutional neural networks (CNNs) in the reconstruction of spectra from truncated FIDs (tFIDs) in 1 H-MRS, which can be valuable in situations in which data sampling is highly limited, such as spectroscopic magnetic resonance fingerprinting. Methods: Rat brain FIDs were simulated at 9.4 T based on in vivo data (N = 11) and randomly truncated by retaining 8,16,32, 64, 128, 256, 512, and 1024 (null truncation) points (denoted as tFID 8 , tFID 16 , … tFID 1024 ). Using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Given the success of the method in different areas, [10][11][12][13][14] DL has been introduced into MRS as an alternative to conventional methods. [15][16][17][18][19][20][21][22] Quantification of MRS datasets has been explored as follows: (1) DL algorithms identify datasets' features and either help reduce the parameter space dimension or set reliable starting conditions for the fit (i.e., combining knowledge on the physics with DL). It showed rapid spectral fitting of a whole-brain MRSI datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Given the success of the method in different areas, [10][11][12][13][14] DL has been introduced into MRS as an alternative to conventional methods. [15][16][17][18][19][20][21][22] Quantification of MRS datasets has been explored as follows: (1) DL algorithms identify datasets' features and either help reduce the parameter space dimension or set reliable starting conditions for the fit (i.e., combining knowledge on the physics with DL). It showed rapid spectral fitting of a whole-brain MRSI datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Other deep learning applications in MRS include spectral reconstruction, denoising, artifact removal, and frequency and phase corrections. [25][26][27][28] Here we propose a novel neural network architecture to directly predict metabolite concentrations without using spectral fitting. We treat quantification of metabolites as a multiclass regression problem that can be effectively solved by deep learning.…”
Section: Introductionmentioning
confidence: 99%
“…The recent success of deep learning (DL), one of the latest machine learning (ML) approaches, in a wide range of tasks, including the MR field, 13 , 14 suggests that it could also handle FPC. Recently, DL‐based solutions have been proposed for metabolite quantification in the frequency domain, 15 , 16 detecting and removing ghosting artifacts, 17 FID reconstruction, 18 automatic peak picking, 19 enhancement of MRSI spatial resolution, 20 and identifying and filtering out poor‐quality spectra. 21 It has been shown that DL can also be used for FPC 7 , 22 and could speed up FPC once it has been successfully trained.…”
Section: Introductionmentioning
confidence: 99%